VAN DER MERWE, P.S. Inventory of documents - VAN DER MERWE, P.S. (ARCA, 2018)
Editor of DIE SUIDWESTER; MP for Middelland (1958-1977); Whip of the National Party (1962-1970); Ballot paperrs and ballot lists, State President election (1967)
COVERAGE 0.02 metre
Keywords: VAN DER MERWE, P.S.; Journalist; National Party